Let Us Make: Interrogating Personnel’s Perception towards Makerspace in a Nigerian University Library - Igbinovia, Magnus Osahon; Alex-Nmecha, Juliet C. (International Journal of Knowledge Content Development & Technology, 2021)
Makerspace offers an innovative way for university libraries to render services and achieve its core objectives. However, there is low level of adoption in Nigerian university libraries, hence the need to investigate the personnel’s perception towards makerspace as an innovative learning platform. To achieve this, the descriptive research design was used to elicit data with the aid of a structured questionnaire, from the 96 library personnel in John Harris Library, University of Benin. Of the 96 copies of questionnaire distributed, 68 copies were returned and analyzed using descriptive statistics. The results showed that the library personnel were familiar with makerspace even though they still require more information about it. Also, that makerspace gives students the opportunity to acquire new skill and enhances collaboration among learners. Moreover, the study revealed that budget constraints, high cost and maintenance of equipments, erratic power supply and lack of staff training are some of the perceived challenges to makerspace implementation. Consequently, the study revealed that university libraries should strategize on how to increase allocation of funds, organize makerspace webinar for personnel, ensure stable electricity supply and create a dedicated space for makerspace in the library. In conclusion, makerspace will provide students with the technological exposure and creative abilities required for the future, and as such effective planning should be made for its deployment and sustainability in Nigerian university libraries. URL: http://ijkcdt.net/xml/29428/29428.pdf